Factors Associated with Missed Hip Fractures - M.D., Timothy J Walden; M.S., Erin A Kelly; M.D., Sanjit R Konda; M.D., Kenneth A Egol (International Journal of Innovative Research in Medical Science, 2021)
Accurate diagnosis and timely care is critical in the treatment of hip fractures in the elderly. Missed or occult hip fractures can be the source of significant morbidity. The purpose of this study was to identify factors associated with an hip fracture that was missed upon a patient’s initial presentation. A retrospective chart review of patients aged 55-100 who presented to a large, academic medical center that acts as a tertiary referral center between January 1, 2015 and October 1, 2018 with a femoral neck or intertrochanteric (IT) hip fracture was performed. An injury qualified as a “missed fracture” if the patient was seen by a provider initially for hip or knee pain but was not initially diagnosed with a hip fracture or presented to our institution for evaluation following unsatisfactory resolution of symptoms elsewhere. A total of 720 patients presented to our medical center with a femoral neck (343) or IT (377) hip fracture between January 1, 2015 and October 1, 2018. Of those patients, 20 (2.9%) were initially “missed”, 15 of which were femoral neck fractures and 5 were IT fractures. Analysis comparing the two groups demonstrated that “missed fracture” types were more likely to be femoral neck fractures (p=0.013), have a baseline altered mental status (p=0.003), be ambulatory to some degree following symptom onset (p<0.001), and report no fall trauma prior symptom onset (p<0.001). No difference was found in rates of complications or mortality. The diagnosis of hip fracture in certain patient populations presenting with complaints of hip or knee pain, with or without a known fall regardless of ambulatory ability should always be considered, especially in the cognitively impaired so that delays in diagnosis and treatment can be avoided. All providers in the chain of care, including ED, primary care, orthopedic, and radiology, need to have a high index of suspicion in these patients in order to ensure that hip fractures are diagnosed in a timely manner.